Unsaturated polyester based composites reinforced with curauá fiber - Preliminary studies - Giacomini, Nestor Pedro; Neis, Angela; Leão, Alcides Lopes [UNESP] (SAE International, 2000)
Curauá fiber processing characterization has been performed throughout the different processing steps. Unsaturated polyester has been used as matrix in the production of curauá reinforced composite samples. Compression molding process has been used to prepare the samples. Tensile strength, impact resistance, flexural strength, Young's modulus and elongation at break have been accessed for curauá composites in comparison with fiberglass composites. Mechanical properties were found not to attend the company's internal standards specification. However, the work has shown some alternatives to solve these problems such as the modification of equipment characteristics and resin formulation, the necessity of incorporation of a higher content of fiber and the possibility of using a new type of filler. Copyright © 2000 Society of Automotive Engineers, Inc.
Keywords: Elongation at break; Equipment characteristics; Fiber processing; Fiberglass composites; Internal standards; Processing steps; Reinforced composites; Unsaturated polyester; Young's Modulus; Compression molding; Esters; Glass fibers; Mechanical properties; Reinforcement; Fibers